IMPLEMENTASI PEMBELAJARAN WEB FACILITATED - Sukma Perdana Prasetya, (Pendidikan Geografi, 2010)
<!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-hyphenate:none; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:AR-SA; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page WordSection1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.WordSection1 page:WordSection1; –> Abstract: Distance education is contemporary process of the education. It facilitates fast, easy delivery of information with its concrete hardware and software tools. The development of high technology, internet and web faclitated delivering become impact of effective using as delivery system to the students. Within the global perspective, even the all work place need educated staff, therefore; there is huge tendency to be education without any time, space, distance limitations from anywhere of the world. Distance Education programs and related web-design should be effective and available in immediate time to catch the students for doing e-learning through the internet connection. If the web faclitated is a tool to deliver information and attract attention of students in order to access e-learning, there should be evaluation and reflections of how this page can be more attractive and informative to be effective. In the study, the scope of the research, there should be the approximate reflections of how web design should be in distance education based on the concrete, approval research study results.